Success of implementation of a systemwide point‐of‐care ultrasound privileging program for emergency medicine faculty. Issue 2 (27th April 2022) - Kennedy, Sarah K.; Ferre, Robinson M.; Rood, Loren K.; Nti, Benjamin; Ehrman, Robert R.; Brenner, Daniel; Rutz, Matt A.; Zahn, Greg S.; Herbert, Audrey G.; Russell, Frances M.
Abstract: Objectives: Point‐of‐care ultrasound (POCUS) is widely used in the emergency department (ED). Not all practicing emergency physicians received POCUS training during residency, leaving a training gap that is reflected in POCUS privileging. The purpose of this study was to evaluate the success of meeting privileging criteria as well as associated factors, following implementation of a basic POCUS training and privileging program within a large emergency medicine department. Methods: We implemented a POCUS training and privileging program, based on national guidelines, for faculty physicians who worked at one of the following EDs staffed by the same emergency medicine department: a pediatric tertiary site, two tertiary academic sites, and seven community sites. POCUS examinations included aorta, cardiac, first‐trimester obstetrics (OB), and extended focused assessment with sonography in trauma. Pediatric emergency medicine faculty were taught soft tissue and thoracic US instead of aorta and OB. Completion of the program required 16 h of didactics, ≥25 quality‐assured US examinations by examination type, and passing a series of knowledge‐based examinations. Descriptive statistics were calculated. Associations between physician characteristics and successfully becoming privileged in POCUS were modeled using Firth's logistic regression. Results: A total of 176 faculty physicians were eligible. A total of 145 (82.4%) achieved basic POCUS privileging during the study period. Different pathways were used including 86 (48.9%) practice‐based, nine (5.1%) fellowship‐based, and 82 (46.9%) residency‐based. POCUS privileging was lower for those working in a community versus academic setting (odds ratio 0.3, 95% confidence interval 0.1–0.9). A greater number of scans completed prior to the privileging program was associated with greater success. Conclusions: Implementation of a POCUS training and privileging program can be successful in a large emergency medicine department that staffs hospitals in a large‐scale health care system composed of both academic and community sites. Faculty physicians with at least some prior exposure to POCUS were more successful.